2017
DOI: 10.7717/peerj.3785
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing healthcare provider respondent fatigue answering a globally administered in-app survey

Abstract: BackgroundRespondent fatigue, also known as survey fatigue, is a common problem in the collection of survey data. Factors that are known to influence respondent fatigue include survey length, survey topic, question complexity, and open-ended question type. There is a great deal of interest in understanding the drivers of physician survey responsiveness due to the value of information received from these practitioners. With the recent explosion of mobile smartphone technology, it has been possible to obtain sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 17 publications
2
78
0
Order By: Relevance
“…For participants of our qualitative study, it was advantageous that the survey only had a few questions, reducing respondent fatigue [47]. In our study we found that most HVTN 915 participants reported quantitatively that their main facilitator in completing the daily mobile phone surveys were the daily SMS reminders.…”
Section: Discussionmentioning
confidence: 76%
“…For participants of our qualitative study, it was advantageous that the survey only had a few questions, reducing respondent fatigue [47]. In our study we found that most HVTN 915 participants reported quantitatively that their main facilitator in completing the daily mobile phone surveys were the daily SMS reminders.…”
Section: Discussionmentioning
confidence: 76%
“…It seems that patients either believed they had nothing to add from previous questionnaires or were experiencing respondent fatigue. Respondent fatigue, also known as questionnaire fatigue, is a common problem in the collection of questionnaire data . Respondents may give less thoughtful answers to questions in the later parts of a questionnaire, prematurely terminate participation, leave text response fields blank or fail to complete it.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that are known to influence respondent fatigue include questionnaire length, questionnaire topic, question complexity and question type. Free text questions tend to induce more fatigue . In the future, these questions could be improved by varying them to better suit the treatment stage and experience of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, there is no consensus on the effect of ethnicity on response, and only 11 responses are made, perhaps indicating that responder fatigue is already in play by this point in the survey [ 44 ].…”
Section: Resultsmentioning
confidence: 99%